Assessment of Various Simulation Models Incorporating Queuing Concept - Bansal, Saloni; Nira, (Journal of Soft Computing Paradigm, 2022)
The investigation of security lines and the stochastic processes that personify them is known as queuing theory. Its goal is to use mathematics to understand real-world scenarios, for example, a massive crowd waiting in line at a bank, or tasks lining up on your smartphone's back end. In linear programming, how long the wait time or line extent is, is regularly hoped to be known which can be achieved using models. The wait does not always correspond to a perfect line; in theory, the first person to arrive will always be served first. Queuing theory is commonly recognized as a branch of operations research, and these models are widely used in development and software implementations. The end purpose of queuing up in queue research is to understand the behaviour and attitude of the underlying architecture so that appropriate strategic decisions can be made. Diverse Structured and Simulation Modelling Systems (SSMS) are described in the study, for example, any logic framework, Arena system, or Bizagi Simulation system.
Keywords: Simulation modeling systems; Arena System (AS); Bizagi Modeler system (BMS); queuing; operations research; strategic selection